MMV006087 is a potent Malaria Box compound against Plasmodium falciparum clinical parasites - Jersley D. Chirawurah; Jersley D. Chirawurah; Bridget Adikah; Bridget Adikah; Felix Ansah; Felix Ansah; Elizabeth Laryea-Akrong; Elizabeth Laryea-Akrong; Harry Danwonno; Harry Danwonno; Collins M. Morang'a; Collins M. Morang'a; et al. (Frontiers Media S.A., 2023)
The emergence of drug-resistant malaria parasites to artemisinin and its partner drugs highlights the need to increase the arsenal of new antimalarials with novel mechanisms of action. To help achieve this aim, this study tested the potency of three Malaria Box compounds (MMV006087, MMV085203, and MMV008956) against five laboratory strains and twenty clinical isolates of Plasmodium falciparum using optimized in vitro growth inhibitory assays. The results were compared to the response from four standard antimalarials-artesunate, chloroquine, mefloquine, and halofantrine. From the results, MMV006087 was the most potent compound with an average IC50 of 22.13 nM compared to MMV085203 (average IC50 of 137.90 nM) and MMV008956 (average IC50 of 262.30 nM). On average, the laboratory strains were also less susceptible to the three Malaria Box compounds (average IC50 of 162.30 nM) compared to the clinical isolates (average IC50 of 135.40 nM). Additionally, MMV006087 was less potent than artesunate but twice more efficacious than chloroquine against the laboratory strains and clinical isolates. The data from this study validate the potency of MMV006087 and MMV085203 as promising antimalarials worthy of further exploration. This study further substantiates the need to include clinical isolates in antimalarial compound screening activities.